2004
DOI: 10.1038/sj.tpj.6500235
|View full text |Cite
|
Sign up to set email alerts
|

A functional genomic study on NCI's anticancer drug screen

Abstract: Pharmacogenomics requires massive computer exploration on heterogeneous databases. COMPARE, the gateway to the NCI's anticancer drug screen database, allows users to correlate drug-sensitivity profiles with a functional genomic database. However, most drugs of known molecular mechanism turn out to be uncorrelated with their molecular-target gene expression. Based on a novel statistical concept, liquid association, we develop an on-line system to identify candidate genes that intervene, confound and weaken the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Previous efforts using this strategy have focused mainly on finding causes of drug resistance. [2][3][4]11,17,18 Gene expression signatures have also been used as surrogate markers of cellular states, for example, to identify agents that induce the differentiation of acute myeloid leukemia cells.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Previous efforts using this strategy have focused mainly on finding causes of drug resistance. [2][3][4]11,17,18 Gene expression signatures have also been used as surrogate markers of cellular states, for example, to identify agents that induce the differentiation of acute myeloid leukemia cells.…”
Section: Introductionmentioning
confidence: 99%
“…Gene co‐expression relationships often exist specifically under certain biological conditions (Lai et al, 2004; Dettling, Gabrielson, and Parmigiani, 2005; Ho et al, 2007), suggesting that rich models of gene interaction will be crucial to continued advancement. Moreover, several studies have suggested that during a biological process the co‐expression patterns within a set of genes may be modulated by the expression level of one or more additional genes (Li, 2002; Li et al, 2004; Li and Yuan, 2004; Zhang, Ji, and Zhang, 2007). Examination of canonical gene pathways provides additional support for this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Toujours dans ces développe-ments bioinformatiques, on peut aussi citer une méthode dénommée « l'association liquide » (liquid association) permettant d'identifier des gènes candidats pouvant interférer avec les corrélations attendues entre la cytotoxicité d'une molécule et l'expression d'un gène cible [14].…”
Section: Introductionunclassified